A dual-responsive polydopamine-modified hydroxybutyl chitosan hydrogel for sequential regulation of bone regeneration. (1st December 2022) - Wan, Zhuqing; Dong, Qinyuan; Guo, Xiaodong; Bai, Xiaoqiang; Zhang, Xiao; Zhang, Ping; Liu, Yunsong; Lv, Longwei; Zhou, Yongsheng
Abstract: Delayed inflammatory reaction and poor osteogenesis are the two main causes of failure for bone-defect healing. Accordingly, in the present study, a dual-responsive hydrogel composite was successfully fabricated in which near-infrared (NIR)-light-responsive polydopamine-coated magnesium‐calcium carbonate microspheres are incorporated into a thermo-responsive hydroxybutyl chitosan hydrogel to provide sequential delivery of the anti-inflammatory drug aspirin and osteogenic bone morphogenetic protein 2 (BMP-2). By initially releasing aspirin rapidly, the hydrogel composite efficiently ameliorates early-stage inflammatory reaction and promotes transition to the regenerative phase. Then, the hydrogel composite allows NIR-light-responsive release of BMP-2, which maximizes its osteoinductive effects. Using an SD rat calvaria-defect model, the sequential and controllable release achieved by the hydrogel is demonstrated to promote new-bone formation. Thus, the current study provides an efficient alternative strategy for developing multifunctional therapeutic biomaterials for bone tissue engineering. Graphical abstract: Unlabelled Image